2012
DOI: 10.1074/jbc.m112.377465
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Cell Adhesion Molecules L1 and CHL1 Are Cleaved by BACE1 Protease in Vivo

Abstract: Background:The function and physiological substrates of BACE1 remain largely unknown. Results: Novel substrates for BACE1 were identified using large scale proteome analysis; L1 and CHL1 were validated in vivo. Conclusion: L1 and CHL1 are physiological substrates for BACE1. Significance: Identification of physiological substrates of BACE1 is important to understand its function and helps to predict potential side effects of BACE1 inhibitor drugs for Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
140
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 87 publications
11
140
0
Order By: Relevance
“…3, A and B ing ϳ180-kDa full-length CHL1 and ϳ170-kDa CHL1 NTF (Fig. 8, A and B, left panels), consistent with previous findings (28,29). Importantly, P7 BACE1 null homogenates exhibited significantly increased intensity of the upper full-length CHL1 band, although the level of the lower CHL1 NTF band was diminished compared with wild type, suggesting that the ϳ170-kDa band did indeed represent BACE1-cleaved CHL1 NTF.…”
Section: Bace1 ϫ/ϫ Hippocampal Mossy Fibers Have Reducedsupporting
confidence: 78%
See 4 more Smart Citations
“…3, A and B ing ϳ180-kDa full-length CHL1 and ϳ170-kDa CHL1 NTF (Fig. 8, A and B, left panels), consistent with previous findings (28,29). Importantly, P7 BACE1 null homogenates exhibited significantly increased intensity of the upper full-length CHL1 band, although the level of the lower CHL1 NTF band was diminished compared with wild type, suggesting that the ϳ170-kDa band did indeed represent BACE1-cleaved CHL1 NTF.…”
Section: Bace1 ϫ/ϫ Hippocampal Mossy Fibers Have Reducedsupporting
confidence: 78%
“…During our study, two groups reported that the neural cell adhesion molecules L1 and CHL1 are novel BACE1 substrates (28,29). Because L1 and CHL1 play important roles in neurite outgrowth and axon guidance (46), we reasoned that these molecules might be involved in the axon targeting defects we have observed in BACE1 Ϫ/Ϫ mice, at least in part.…”
Section: Bace1 ϫ/ϫ Hippocampal Mossy Fibers Have Reducedmentioning
confidence: 98%
See 3 more Smart Citations